Australian students' experiences of sexuality education at school. Issue 5 (3rd September 2019) - Ezer, Paulina; Kerr, Lucille; Fisher, Christopher M.; Heywood, Wendy; Lucke, Jayne
ABSTRACT: Sexuality education is a trusted source of information and guidance for adolescents and young people on sexual health, sexuality and relationships, and it can improve the sexual health of this population. Such education is most effective when informed by the views of young people themselves; however, there is limited research that investigates young people's experiences of school-based sexuality education. This paper presents findings related to sexuality education from the Fifth National Survey of Secondary Students and Sexual Health, which surveyed 2, 193 Australian Year 10, 11 and 12 students from diverse school systems. Descriptive analyses were used to describe the nature of sexuality education the students report having received. Chi-square and T-test analysis were used to determine associations between the relevance of sexuality education, the nature of sexuality education and demographic characteristics, as well as associations between students' knowledge of HIV, STIs and HPV and their receipt of sexuality education. Additionally, a thematic analysis of the open-ended qualitative responses was performed to provide additional context to the quantitative results. Findings from the study elucidate students' own perceptions of their school-based sexuality education and provide valuable insight for designing and implementing school-based sexuality education based on students' opinions and needs.